EVALUATING THE EFFECTIVENESS OF LAPAROSCOPIC SURGERY IN ELDERLY PATIENTS: RISKS, BENEFITS AND POSTOPERATIVE RESULTS - Pedro do Valle Varela, João; de Oliveira Figueiredo, Bruno; Roschy da Silva Costa, Vinicius; Sobrinho Vaz, Natália; Henrique de Melo Almeida, Thomas; Silva de Oliveira Bernardes, Gabriel; Rodrigues de Almeida, Letícia; Luiza Fonseca Maia Caetano, Ana (Health and Society, 2024)
Laparoscopic surgery has established itself as a minimally invasive approach that offers several advantages over open surgery, including less post-operative pain, faster recovery and lower risks of complications. However, the effectiveness of laparoscopic surgery in elderly patients, who often have comorbidities and distinct physiological characteristics, is a growing area of interest. This abstract examines the risks, benefits and post-operative results of laparoscopic surgery in elderly patients, providing a critical overview of its applicability and effectiveness in this population. The aim of this paper is to evaluate the effectiveness of laparoscopic surgery in elderly patients, analyzing the main risks, benefits and postoperative outcomes associated with this approach. The intention is to provide a comprehensive overview that will help in clinical decision-making and in improving surgical practices for this age group. This study carries out a literature review on laparoscopic surgery in elderly patients, analyzing the benefits, risks and long-term results associated with this procedure. The aim is to provide a comprehensive overview of the positive aspects and challenges of minimally invasive surgery for the geriatric population. Laparoscopic surgery offers several advantages for elderly patients, including smaller incisions, less postoperative pain and a faster recovery. These benefits are particularly important in the elderly, who may have a slower recovery after open surgery and a higher risk of complications. However, elderly patients often have comorbidities such as cardiovascular disease, diabetes and functional impairment, which can increase the risk of complications during and after the laparoscopic procedure. Studies show that although laparoscopic surgery can reduce the length of hospitalization and improve functional recovery, these patients can still face specific challenges, such as a greater propensity to respiratory complications and difficulties in healing. As a result, the effectiveness of laparoscopic surgery in the elderly can also be influenced by the experience and skill of the surgeon, as well as the appropriateness of patient selection. Rigorous preoperative assessment and consideration of individual factors are crucial to minimizing risks and optimizing results. Studies indicate that careful patient selection and the suitability of laparoscopic techniques to meet the specific needs of the elderly are essential to maximize the benefits of this approach. Post-operative results generally include faster recovery and less pain compared to open surgery. However, long-term analysis is essential to assess ongoing efficacy and the incidence of late complications, such as adhesions or complications associated with pre-existing conditions. It is concluded that laparoscopic surgery offers significant benefits for elderly patients, such as less postoperative pain and faster recovery, compared to open surgery. However, the increased complexity due to comorbidities and the physiological characteristics of elderly patients can lead to additional risks and specific challenges. Careful patient selection, detailed preoperative assessment and the surgeon’s experience are determining factors for the success of laparoscopic surgery in this population. Although the minimally invasive approach has demonstrated overall efficacy, it is essential to continue monitoring long-term results and to adapt surgical practices to meet the unique needs of elderly patients.